The trend of road traffic crashes at urban signalised intersection - Nurul Farhana, Nasarrudin; Intan Suhana, Mohd Razelan (IOP Publishing, 2018)
Road traffic crash is one of the main contributing factors for deaths in the world. Intersection is listed as the second road type which road crashes occurred frequently. Hence, the traffic light was installed to minimise the road crashes at intersection. However, the crashes are still occurring and arising. The objective of this study was to exhibit the trend of road crashes at the signalised intersections. The data of road crashes for the past 6 years were analysed using descriptive analysis. The results showed that the road traffic crashes at three- and four-legged signalised intersection recorded the increasing trend. In conclusion, this finding shows that the road traffic crashes for these types of signalised intersection in Malaysia is rising. It is also one the contributors to the increasing number of crashes in Malaysia. This finding will encourage the local authority to conduct awareness programs on the safety at the signalised intersection.